Long-term follow-up of a randomized clinical trial comparing glycemic excursion minimization (GEM) to weight loss (WL) in the management of type 2 diabetes. Issue 2 (29th November 2021) - Cox, Daniel J; Oser, Tamara; Moncrief, Matthew; Conaway, Mark; McCall, Anthony
Abstract : Introduction: We previously reported the physical, psychological and behavioral 3-month post-treatment results of a randomized controlled trial comparing glycemic excursion minimization (GEM) versus conventional weight loss (WL) therapy in the management of type 2 diabetes (T2D). GEM is a paradigm shift in the lifestyle management of T2D that focuses on reducing postnutrient glucose excursions, rather than reducing weight. We now present the 13-month follow-up results. Research design and methods: The initial study sample of 172 were 30–80 years old, had T2D for ≤10 years, an HbA1c ≥6.8% (51 mmol/mol), and were not using insulin. Participants were randomized to 6 hours of group treatment, either to WL or one of three versions of GEM. GEM groups differed in degree of blood glucose (BG) feedback provided during treatment: no recommended feedback, systematic capillary BG feedback before and after nutrient intake and physical activity, or continuous glucose monitoring. Since these GEM groups did not differ in pre-post improvement they were combined for initial and current analyses. Of those who completed the 3-month postassessment, 100% and 96% of the WL and GEM participants completed the 13-month follow-up assessment. Results: Pre to follow-up within-group comparisons indicated WL participants sustained improvement in body mass index (BMI) (−0.9±1.4, p=0.001). GEM participants continued to benefit in their HbA1c (−0.5±1.4, p<0.001), BMI (−1±1, p<0.001), high-density lipoprotein (p<0.001), reduction of carbohydrate ingestion (p<0.001), self-monitoring of blood glucose satisfaction (p<0.001) and frequency (p<0.001), diabetes knowledge (p<0.001), diabetes empowerment (p<0.001), and both diabetes distress emotional (p=0.009) and regimen (p=0.001) subscales. Forty-two percent and 52% of WL and GEM participants, respectively, were classified as responders (individuals whose A1c dropped by at least −0.5%), with a mean HbA1c reduction of −1.2% and −1.5%. Neither WL nor GEM responders differed from non-responders in baseline demographics, psychological or disease severity variables. While WL responders could not be predicted, 73% of GEM responders were predicted by post minus pretreatment reductions of HbA1c, diabetes medication and BMI. Conclusions: While WL sustained improvement in BMI, GEM sustained benefits across a broad range of physical, behavioral and psychological parameters, beneficial for clinicians and adults with T2D. This may be especially relevant for primary care physicians who manage about 90% of patients with T2D. Trial registration number: NCT03196895 .